Two new species of Billolivia (Gesneriaceae) with yellow flowers from Vietnam - Trường, Lưu Hồng; Đăng, Trần Hữu; Nhân, Phạm Hữu; Trung, Nguyễn Trần Quốc; Đạt, Nguyển Quốc; Long, Vũ Ngọc (Phytotaxa, 2018)
Billolivia citrina and B. yenhoae are described as new species of Gesneriaceae from Central Vietnam. They are the first taxa of the genus known to have yellow corolla lobes. A key to all eleven species of the genus is given.